Training Parents of Hard Core Delinquents as Behaviour Managers of their Children - Csapo, Marg; Friesen, John (Canadian Journal of Counselling and Psychotherapy, 2012)
This study measured the effectiveness of a behaviour modification training program with parents of hard core delinquents. Ten parents of hard core delinquents were assigned to an experimental group andten to a control group. Both groups completed the Walker Problem Behavior Identification Checklist before and after the study. The comparison between the pre-and post-testing showed statistically significant differences for the experimental group. Parents of the experimental group were assisted with designing and carrying out behaviour management projects with their deviant children. Twenty-eight projects were completed. A parenting fee was paid to participants with a bonus for improved parenting.